1984
DOI: 10.1037/0022-3514.47.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Sex role attributes, symptom distress, and defensive style among college men and women.

Abstract: Eighty-four male and 90 female college students completed the PRF-Andro masculinity and femininity scales, a symptom checklist, and a defense mechanism inventory. Results indicated that interrelations among sex role attributes, defense preferences, and symptom distress differed for men and women. Cross-sex-typed persons mostly accounted for differences in symptom distress within each sex: Masculine women reported relatively low and feminine men reported relatively high degrees of symptom distress. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Cohort comparisons of college-aged men and women indicate that androgyny scores increased in the decade following the women's movement (Heilbrun and Schwartz 1982;Pederson and Bond 1985), and have continued to increase as a function of historical time with women's scores showing greater increases than those of men (Frank et al 1984;Twenge 1997). This research suggests that for women, socio-cultural changes associated with the second wave of the women's movement may be reflected in the integration of masculine traits with feminine traits.…”
Section: Androgynous Traitsmentioning
confidence: 74%
“…Cohort comparisons of college-aged men and women indicate that androgyny scores increased in the decade following the women's movement (Heilbrun and Schwartz 1982;Pederson and Bond 1985), and have continued to increase as a function of historical time with women's scores showing greater increases than those of men (Frank et al 1984;Twenge 1997). This research suggests that for women, socio-cultural changes associated with the second wave of the women's movement may be reflected in the integration of masculine traits with feminine traits.…”
Section: Androgynous Traitsmentioning
confidence: 74%
“…In thinking about these gender differences, it is interesting to contrast the description of these women who use projection, with that of women who use the more typically female defense of "turning against the self" (TAS) (e.g., Cramer, 1991a;Cramer & Carter, 1978;Gleser & Ihilevich, 1969;Massong, Dickson, Ritzler, & Layne, 1982). TAS is associated, for both men and women, with self-blame, low self-esteem, maladjustment, symptom distress, and suicide attempts (e.g., Frank, McLaughlin, & Crusco, 1984;Ihilevich & Gleser, 1986;Scholz, 1973). TAS is also positively associated with a feminine sex role orientation (Cramer & Carter, 1978;Evans, 1982;Frank et al, 1984;Gleser & Ihilevich, 1969;Lobel & Winch, 1986), while projection is negatively associated with a feminine orientation (Levit, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…TAS is associated, for both men and women, with self-blame, low self-esteem, maladjustment, symptom distress, and suicide attempts (e.g., Frank, McLaughlin, & Crusco, 1984;Ihilevich & Gleser, 1986;Scholz, 1973). TAS is also positively associated with a feminine sex role orientation (Cramer & Carter, 1978;Evans, 1982;Frank et al, 1984;Gleser & Ihilevich, 1969;Lobel & Winch, 1986), while projection is negatively associated with a feminine orientation (Levit, 1991). However, Levit (1991) demonstrated that the association between TAS and feminine orientation was due to the component of passive-dependency, rather than to that aspect of femininity representing "communion.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between DMI scales and acknowledgment of various psychological symptoms was investigated by Frank, McLaughlin, and Crusco (1984). For both men and women college students, TAS was positively related to symptom distress, while PRN and REV were negatively associated.…”
Section: Questionnaire Pathologymentioning
confidence: 93%